Saudi Arabia’s Foreign Policy Towards Turkey During and After Arab Uprising: A Defensive Realism Approach - Kural, Muzaffer; Erdem, Gökhan (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2022)
The Arab Uprisings in 2011 have led to redistribution of power in the Middle East. It has brought challenges and opportunities for regional powers such as Saudi Arabia and Turkey. While Turkey has perceived the developments as an opportunity to increase its influence in the region, it has created threat perceptions for Saudi Arabia’s hegemony in the Middle East. Especially, due to Turkey’s rising influence in Egypt and Syria it has been perceived as a second rival, after Iran, by Riyadh. This article argues that due to Turkey’s rising power in Egypt and Syria, Saudi Arabia’s foreign policy towards Turkey has been shifting by supporting local actors in Egypt and Syria in order to maintain the status quo. The paper aims to analyze shifts in Saudi Arabia’s foreign policy towards Turkey during and post-Arab uprisings in the Middle East in the framework of defensive realism through the regional level of analysis.

Wydarzenia arabskiej wiosny 2011 roku doprowadziły do redystrybucji władzy na obszarze Bliskiego Wschodu. Stworzyło to nowe wyzwania i możliwości dla mocarstw regionalnych, takich jak Arabia Saudyjska i Turcja. Turcja postrzegała arabską wiosnę jako okazję do zwiększenia swoich wpływów w regionie, tworząc tym samym poczucie zagrożenia u roszczącej sobie hegemoniczne aspiracje na Bliskim Wschodzie Arabii Saudyjskiej. Turcja, zwiększając swoje wpływy w Egipcie i Syrii zaczęła być postrzegana przez Rijad jako drugi po Iranie najważniejszy rywal w regionie. Artykuł dowodzi, że ze względu na rosnącą pozycję oraz wpływy Turcji w Egipcie i Syrii, polityka zagraniczna Arabii Saudyjskiej wobec Turcji zmienia się poprzez wspieranie lokalnych aktorów w Egipcie i Syrii w celu utrzymania status quo. Artykuł ma na celu analizę zmian w polityce zagranicznej Arabii Saudyjskiej wobec Turcji w trakcie i po wydarzeniach arabskiej wiosny na Bliskim Wschodzie w ujęciu paradygmatu realizmu defensywnego.
Polityka zagraniczna Arabii Saudyjskiej wobec Turcji w okresie Arabskiej Wiosny oraz po jej zakończeniu w ujęciu realizmu defensywnego
Keywords: Saudi Arabia; Turkey; Defensive Realism; Arab Uprisings; Egypt; Syria; Arabia Saudyjska; Turcja; realizm obronny; powstania arabskie; Egipt; Syria